Vibration monitoring of a grandstand in Dragon Stadium - H. Marques (2007)
The present communication focuses on the importance of the dynamic actions induced by groups of people with synchronous movements and the need to perform dynamic analysis in the corresponding structural elements. Special attention herein is given to the case of stadium structures. The continuous optimization in structural design made possible, in certain cases, to resist to high loading values in ultimate limit states but still have serviceability deficiencies. Problems with excessive vibration on recently built structures have been reported (SCOSS 2001). This can cause human discomfort, crowd panic or collapse of the structure. Simple methods like adopting a frequency threshold cannot always be applied since they may result in a substantial increment in cost or are impossible to accomplish due to architectural constraints. This is the reason why it is unavoidably necessary to model and evaluate the dynamic response of certain structures. This article presents also some results of the monitoring of two events in a grandstand on Dragon Stadium in operating conditions.